Photocatalytic removal of Malachite Green through ZnO/CeO2 nanocomposite catalyst - Lipika Das Samanta, Somak Joyti Sahu , Sutapa Roy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Processes (AOPs) have been developed to convert non-biodegradable contaminants into harmless species. Heterogeneous photocatalysis, a novel process belonging to the class of AOPs, via combination of photocatalysts, such as phtotcatalyst and ultraviolet (UV) light, is as an attractive alternative treatment method for the removal of toxic pollutants from wastewater, owing to its ability to degrade the pollutants into innocuous end-products, such as CO2, H2 and mineral acids. In the present work, the synthesized photocatalyst was used for removal of Malachite green (MG) through photocatalytic reaction. The ZnO/CeO2 photocatalyst was prepared by co-precipitation method. The prepared catalyst was synthesized by scanning electron microscopy and BET surface analyzer. The activity of catalyst was observed. The various process parameters such as calayst loading, concentration of dye, irradiation time, pH of reaction solution were also observed. Influence of energy source and oxidizing agent were also seen. So, photocatalysis are considered very highlt competitive water treatment technologies for removal of dye.